Magnetic field sensor using tilted fiber grating interacting with magnetic fluid - Zheng, Jie (2013)
A novel magnetic field sensor using tilted fiber Bragg grating (TFBG) interacting with magnetic fluid is proposed and experimentally demonstrated. The TFBG is surrounded by magnetic fluid whose complex refractive index changes with external magnetic field. The guiding properties of cladding modes excited by the TFBG are therefore modulated by the external magnetic field. As a result, the magnetic field strength measurement is successfully achieved within a range up to 196 Gauss by monitoring extinction ratio of cladding mode resonance. Furthermore, temperature variation can be obtained simultaneously from the wavelength shift of the TFBG transmission spectrum.